Shaping the futures of (vocational) education and work - Molzberger, Gabriele [Herausgeber]; Wahle, Manfred [Herausgeber] (Peter Lang, 2015)
"Education and work are moving towards an open, but uncertain future. Research on vocational and continuing education constantly needs to reassure the conditions of educational systems, current concepts of VET and work, educational policies, and its own assumptions in ascertaining theory of VET. In this context, modernisation is a significant paradigm. It refers to new ideological, socio-economic, structural and institutional qualities.This volume analyses interdependencies and complexities of research, politics and practice of vocational, further and continuing education. With contributions from European VET researchers it assembles critical reflective, empirical, cross-cultural and historical perspectives. The volume discusses the dynamic changes of work and education both in regional and global labour markets. Central issues are transformations of vocational education and work, the impacts of gender, ethnicity, culture and globalization as well as the anticipation of possible futures of vocational education and work." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; G 2.4 Sozialer Wandel; G 2.1 Globalisierung; Berufsbildung; Arbeitswelt; Zukunftsperspektive; Bildungspolitik; Bildungsforschung; Sozialer Wandel; Kulturwandel; Globalisierung